The Transformation of Arabic Learning Language Majors in High School - Linda Ayu Khuroidah; Taufik (Universitas Yudharta Pasuruan, 2022)
Curriculum changes have an impact on Arabic language learning in high school. Emergence of Permendikbud regulations related to changes in the new learning process, has also changed the interest in Arabic subjects or language majors in high school. The transformation of Arabic learning in the high school language department is the reason why this research is important, namely to answer doubts and provide an overview of the Arabic language learning system in high school with the application of an independent curriculum. By using qualitative analysis techniques based on literacy data, this study collects data from Permendikbud Number 37 of 2018 and Permendikbud Number 56 of 2022. By obtaining the following research results; First, learning Arabic in high school with the latest curriculum (merdeka curriculum) has eliminated the existence of language specialization majors or classes. Where Arabic language learning has been applied to all students and levels without any differences in the two specialization subjects, Arabic language learning has undergone a transformation and transition from K-13 to an independent curriculum, thus making teachers implement a differentiated learning system. In this case, especially in the learning model that trains the four maharoh, the process and results of student achievement are certainly different.